The Effect Of Managerial Ownership On Company Values Mediated By Profit Quality - Mardiana, Ana; Daromes, Fransiskus. E.; Kresensia, Vince (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2024)
The purpose of this research is to analyze the effect of managerial ownership on firm value which is mediated by earnings quality by using agency theory. The population used in this study were manufacturing companies listed on the Indonesia Stock Exchange with a total research period of 2019-2021. The population in this study totaled 157 companies, the sample selection used a purposive sampling technique so that a total of 56 companies were obtained. The analysis used in this study is regression and path analysis with mediation testing using sobel calculations. The findings obtained from this study can be concluded that managerial ownership has a significant effect on firm value, managerial ownership has a significant effect on earnings quality, earnings quality has a significant effect on firm value and earnings quality is able to mediate the effect of managerial ownership on firm value